A phylogenomic analysis of Culicomorpha (Diptera) resolves the relationships among the eight constituent families. (26th February 2018) - NARAYANAN KUTTY, SUJATHA; WONG, WING HING; MEUSEMANN, KAREN; MEIER, RUDOLF; CRANSTON, PETER S.
Abstract: Culicomorpha is a particularly species‐rich clade within Diptera (true flies) that comprises c . 10% of the described diversity, including many medically important flies. Morphological studies – even when all life stages are included – yield relationships different from those derived from molecular data, notably with regard to the position of Chironomidae. Congruence amongst molecular studies has been weak due to limitations in gene‐ and family‐level taxon coverage. Here we use a whole‐transcriptome shotgun phylogenomic approach to clarify the relationships among all families of Culicomorpha. The dataset comprised 30 species (27 ingroup) and 364 888 amino acid residues for 1233 single‐copy protein‐encoding genes. Likelihood and parsimony analyses produce robust and highly congruent phylogenetic trees, with only one node in conflict. The superfamily Culicoidea is well supported and comprises Dixidae + [Corethrellidae + (Chaoboridae + Culicidae)]. As suggested previously, Chironomoidea is not monophyletic. The well supported Thaumaleidae + Simuliidae is sister group to Culicoidea, with the weakly supported Chironomidae + Ceratopogonidae probably being the sister group of all remaining Culicomorpha. We used random addition concatenation analysis (RADICAL) and four‐cluster likelihood mapping (FcLM) to assess the strengths of nodal support. The sister‐group relationship between Chironomidae + Ceratopogonidae is consistent with the FcLM results but support for this relationship emerges only when 1150 of the 1233 loci are analysed. We discuss briefly nodes that remain poorly supported even with thousands of genes and mention problems with vouchering in transcriptomic studies. Abstract : We reconstruct the relationships among the eight constituent families of the species‐rich Culicomorpha (Diptera) clade using a phylogenomic approach. Different analysis strategies produce robust and highly congruent phylogenetic trees, with only the positions of the Chironomidae and Ceratopogonidae in conflict. Culicoidea is monophyletic and comprises Dixidae, Corethrellidae, Chaoboridae and Culicidae; Thaumaleidae + Simuliidae is the sister group of the Culicoidea.